Improving the thermal performance of the buildings using a green façade system: An experimental study in a tropical climate - Widiastuti Ratih; Zaini Juliana; Abid Muhammad; Pramesti Previari Umi (E3S Web of Conferences)
The green façade systems can be considered as an effective way to create sustainable building design through improving building thermal performance. The significant temperature decrease can significantly decrease the building temperature and enhancing energy efficiency for cooling load. An experimental study of the vertical greenery system was conducted at the Faculty of Integrated Technologies, Universiti Brunei Darussalam, Brunei Darussalam to evaluate the thermal impact of a green façade on the building by varying the wall surface and room temperature. Two identical rooms were identified as green façade rooms (GF-Room) and bare wall room (BW-Room). The temperature variation shows that the GF-Room consistently had lower temperatures than BW-Room. The notable drop in temperature is due to the shading effect of the green façade, as shown by the ambient air temperature in the cavity between the green façade system and the GF-Room. The mean and maximum temperature reduction is observed to be 2.2°C and 19.8°C, respectively. While the indoor thermal parameters showed a smaller temperature reduction by an average of 1.0°C. The findings of the current study led to the conclusion that using a vertical greenery system as a passive cooling design can significantly contribute to the temperature reduction of the buildings.